Dance your pants off! - Krulik, Nancy E.; Blecha, Aaron (New York : Grosset & Dunlap, 2013)
George and his classmates are excited to learn that their teacher, Mrs. Kelly, will appear on a televised dance show, but when they go to see a taping, the Super Burp proves it is not camera-shy.
Keywords: Behavior -- Fiction; Belching -- Fiction; Dance -- Fiction; Reality television programs -- Fiction; Schools -- Fiction; Magic -- Fiction